SCHWANNOMA CERVICAL: A PROPÓSITO DE UM CASO CLÍNICO - Moura, João Elói; Rodrigues, Fernando; Bastos, José; Quadros, Jorge; Rodrigues, Manuel Filipe (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.